The Potential Cost-Effectiveness and Equity Impacts of Restricting Television Advertising of Unhealthy Food and Beverages to Australian Children - Brown, Vicki (Nutrients, 2018)
Television (TV) advertising of food and beverages high in fat, sugar and salt (HFSS) influences food preferences and consumption. Children from lower socioeconomic position (SEP) have higher exposure to TV advertising due to more time spent watching TV. This paper sought to estimate the cost-effectiveness of legislation to restrict HFSS TV advertising until 9:30 pm, and to examine how health benefits and healthcare cost-savings differ by SEP. Cost-effectiveness modelling was undertaken (i) at the population level, and (ii) by area-level SEP. A multi-state multiple-cohort lifetable model was used to estimate obesity-related health outcomes and healthcare cost-savings over the lifetime of the 2010 Australian population. Incremental cost-effectiveness ratios (ICERs) were reported, with assumptions tested through sensitivity analyses. An intervention restricting HFSS TV advertising would cost AUD5.9M (95% UI AUD5.8M–AUD7M), resulting in modelled reductions in energy intake (mean 115 kJ/day) and body mass index (BMI) (mean 0.352 kg/m(2)). The intervention is likely to be cost-saving, with 1.4 times higher total cost-savings and 1.5 times higher health benefits in the most disadvantaged socioeconomic group (17,512 HALYs saved (95% UI 10,372–25,155); total cost-savings AUD126.3M (95% UI AUD58.7M–196.9M) over the lifetime) compared to the least disadvantaged socioeconomic group (11,321 HALYs saved (95% UI 6812–15,679); total cost-savings AUD90.9M (95% UI AUD44.3M–136.3M)). Legislation to restrict HFSS TV advertising is likely to be cost-effective, with greater health benefits and healthcare cost-savings for children with low SEP.